Child Welfare : Connecting Research, Policy, and Practice. - Kufeldt, Kathleen (Wilfrid Laurier University Press, 2006)
The second edition of [http://www.wlupress.wlu.ca/Catalog/kufeldt-2.shtml Child Welfare: Connecting Research, Policy, and Practice] will be available in April 2011. Click under By the same editor in the right column or visit the [http://www.wlupress.wlu.ca/Catalog/kufeldt-2.shtml webpage] for more information and to order. In 1994 a group of researchers and decision makers met to discuss the state of child welfare. Also present were a few practitioners and two youth in care. Six years later, when they met again, the number of practitioners and youth had grown considerably and were joined by.